The ἂτοπα of Elagabalus. - Merli, Olivia (Helios)
Cassius Dio referred to the sexual excesses and behaviors of the emperor Elagabalus as ἂτοπα ("strange things"), and scholars ever since have grappled with the problem of how best to interpret Cassius Dio's account of Rome's most reviled emperor. In this article I offer a new contextualization of Cassius Dio's and other related accounts of Elagabalus with the goal of developing a deeper appreciation of both the gender regime of the period and the emperor's place within it. To accomplish this, I draw first on contemporary or near contemporary medical texts that cast new light on Elagabalus's desire to have an αἰδῶ γυναικείαν ("female sexual organ") contrived for himself. Then, drawing on numismatic and archeological evidence, I give considerable attention to the religious innovations of the period. Crucially, in his efforts to bridge the human and the divine, to invest women with unprecedented prominence in Roman public religion, and to fashion a new religious identity which also entailed the transformation of his body, Elagabalus was bound to scandalize his more traditionally minded contemporaries. Finally, as I argue in the conclusion, transgender studies--which enable an understanding of such behaviors as part of a search for a new identity outside the traditional gender binaries--offer a powerful lens through which to develop a deeper understanding of Elagabalus in relation to the cultural dynamics of the period.